The Role of School Principals in Improving the Quality of Learning - Maulana, Irwan; Rizal Mz, Syamsul; Anas, Azwar (Annpublisher, 2024)
SMK, an educational institution focused on producing graduates capable of finding employment, pursuing further study, or starting their own business, becomes a strategically crucial educational institution to generate graduates prepared for the workforce. This study clarifies how school principals might raise the standard of instruction at SMKN 1 Ciomas. A descriptive qualitative research method was employed. At SMKN 1 Ciomas Bogor, this study was carried out. The head of the study program, students, the vice principal of curriculum and student affairs, and the principal were all interviewed. Every document about the research issue is examined through document studies. Data reduction, data presentation, data verification, and data collecting are all used in data analysis procedures. As part of his leadership responsibilities, the principal of SMKN 1 Ciomas plans and develops programs for teachers and students. He then works with businesses and industry to implement the programs and provides orientation to goods and services. Finally, he supervises and evaluates the students' learning as it occurs.